Double-sided release film
By setting a separation layer with specific parameters on both sides of the resin film, the problem of surface roughness and peeling state control in thin resin film manufacturing is solved, the stability and reliability of the resin film during the winding process is realized, and the production efficiency and product quality are improved.
Patent Information
- Application Number
- JP2020148314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-03
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-09-03
Smart Images

Figure 0007624155000004 
Figure 0007624155000001 
Figure 0007624155000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a double-sided release film having release layers on both sides of a base film. [Background technology]
[0002] In manufacturing processes such as forming double-sided adhesive tape, forming green sheets for ceramic capacitors, forming anisotropic conductive films, and forming insulating resin sheets for circuit boards, there is a process in which a resin film containing each raw material (hereinafter sometimes simply referred to as "resin film") is formed on the surface of a film with release properties and then rolled up, and double-sided release films are widely used as substrates in the manufacturing process. All of the functional sheets obtained from resin films are undergoing technological innovation toward thinner films, and it is becoming necessary to improve the release films to be suitable for the manufacturing process of thinner functional sheets.
[0003] For example, an adhesive anisotropic conductive film is widely used as a material for bonding two circuit elements and electrically connecting the terminals between them. This anisotropic conductive film is made of an insulating adhesive with conductive particles dispersed therein, and is sandwiched between the terminals of the elements to be connected and then thermocompression-bonded, thereby simultaneously bonding the elements together and electrically connecting the terminals.
[0004] The manufacturing method of this anisotropic conductive film is usually to apply and dry an adhesive varnish, which is made by mixing and dispersing conductive particles in an insulating adhesive made by mixing insulating resin such as epoxy resin and hardener, on a carrier film (separator). After applying and drying the varnish, the carrier film is rolled up and cut to an appropriate width for use. Since anisotropic conductive films with adhesive properties are sticky under normal conditions, it is necessary to provide a release layer on both sides of the carrier film. Furthermore, it is necessary to provide a difference in peel strength when peeling the anisotropic conductive film between the inner side and the outer side of the roll. If both sides of the carrier film are treated with the same release treatment, the anisotropic conductive film may be taken to the unwinding roll or a gap may occur between the carrier film and the anisotropic conductive film, causing problems such as not being able to be pulled out smoothly.
[0005] On the other hand, if the surface unevenness of the polyester film is too large in association with the thinning of the anisotropic conductive film, the anisotropic conductive film will not be formed uniformly, resulting in problems such as poor conductivity. For this reason, Patent Document 1 discloses a release film for producing an anisotropic conductive film, in which the peel strength of both surfaces is within a predetermined range, and the center line average roughness Ra of the release layers on both surfaces is set to 0.1 to 1.0 μm. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 4495880 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in recent years, there is a tendency for the thickness of image display devices to be reduced, and resin films such as anisotropic conductive films are required to be further thinned. For this reason, according to the study by the present inventors, when a thinner resin film is formed, the release film having a center line average roughness Ra in the range described in Patent Document 1 has too large overall unevenness, which tends to cause protrusions higher than the surroundings, and the surface condition of the resin film is poor due to paint repellency starting from the high protrusions. In addition, when a thinner resin film is formed, it has been found that if the peeling force of both surfaces is not sufficiently controlled, the peeling condition is likely to deteriorate when the rear release layer is peeled off from the resin film when unwound from the roll.
[0008] Therefore, an object of the present invention is to provide a double-sided release film that can improve the surface condition of the resulting resin film and the peeling condition of the resin film when unrolled, even when a thinner resin film is formed. [Means for solving the problem]
[0009] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the above-mentioned object can be achieved by controlling not only the surface roughness Ra, which is an index of the overall unevenness of a polyester film, but also the maximum protrusion height Rp within a specified range of area, and thus arrived at the present invention.
[0010] That is, the present invention includes the following.
[0011] <1> A release layer A, a polyester film, and a release layer B, in this order; A double-sided release film characterized by satisfying the following formulas (1) to (6): Ra<0.1 (1) RpA<2.0 (2) RaB ≧ 0.85 × RaA (3) RpB ≥ 0.85 × RpA (4) 1.5≦HA / HB≦100 (5) 0.15≦HA+HB≦7 (6) In the formulas (1) to (6), RaA represents the center surface average roughness (μm) of the surface of release layer A, RaB represents the center surface average roughness (μm) of the surface of release layer B, RpA represents the center surface maximum protrusion height (μm) of the surface of release layer A in an area of 283 μm x 213 μm, RpB represents the center surface maximum protrusion height (μm) of the surface of release layer B in an area of 283 μm x 213 μm, HA represents the peel force of the surface of release layer A (N / 25 mm width), and HB represents the peel force of the surface of release layer B (N / 25 mm width).
[0012] <2> An antistatic layer is included between at least one of the release layer A and the release layer B and the polyester film, and the surface resistivity of the surface of the release layer on the side where the antistatic layer is provided is 5×10 4 ~5×10 12 Ω / □ <1> The double-sided release film according to claim 1.
[0013] <3> The polyester film contains inorganic particles having an average particle size of 0.1 to 2.0 μm. <1> or <2> The double-sided release film according to claim 1.
[0014] <4> The content of the inorganic particles is 0.05 to 25% by mass. <3> The double-sided release film according to claim 1.
[0015] <5> The antistatic layer contains at least one selected from the group consisting of conductive polymers, metal oxide particles, and polymers to which a quaternary ammonium salt has been added. <1> ~ <4> 2. The double-sided release film according to claim 1 . Effect of the Invention
[0016] According to the double-sided release film of the present invention, even when a thinner resin film is formed, it is possible to provide a double-sided release film that can improve the surface condition of the resulting resin film and the peeling condition of the resin film when unrolled. Therefore, for example, it can be suitably used as a carrier film in the process of forming a resin film that is a raw material for various functional sheets, or as a separator during winding. [Brief description of the drawings]
[0017] [Figure 1] 1A and 1B are cross-sectional views showing the schematic structures of examples of double-sided release films of the present invention, where FIG. 1A corresponds to Example 1 and FIG. 1B corresponds to Example 4. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. For convenience of explanation, the film-forming direction of the film may be referred to as the machine axis direction, longitudinal direction, longitudinal direction, or MD direction, and the direction perpendicular to the film-forming direction and the thickness direction may be referred to as the width direction, transverse direction, or TD direction.
[0019] (Schematic structure of double-sided release film) The double-sided release film of the present invention contains, in this order, a release layer A, a polyester film, and a release layer B. The term "polyester film" refers to a film containing 50% by mass or more of polyester resin, based on the mass of all resin components, in a single layer when formed as a single layer, or in all layers when formed as multiple layers, and preferably 70% by mass or more.
[0020] In the present invention, as shown in Figures 1(a) to (b), it is assumed that a resin film 5 is formed on the side of the release layer A2A, and a release layer B2B is provided on the back side of the polyester film 1.
[0021] 1(b), an antistatic layer 3 may be interposed between the release layer A2A and the polyester film 1, or between the release layer B2B or between both the release layer A2A and the polyester film 1. However, from the viewpoints of process simplification and antistatic effect during peeling, it is preferable that the antistatic layer 3 is interposed only between the release layer A2A and the polyester film 1.
[0022] The polyester film may have a single layer structure as shown in FIG. 1(a), or may have a three-layer structure of a microparticle-containing layer / microvoid-containing layer / microparticle-containing layer, or a two-layer structure of a microparticle-containing layer / microvoid-containing layer. The polyester film may have another layer laminated on the microparticle-containing layer or the microvoid-containing layer. The polyester film may have a three-layer structure of a microvoid-containing layer / microparticle-containing layer / microvoid-containing layer, or a four-layer or more structure in which the microvoid-containing layer / microparticle-containing layer is repeated. In any laminate structure, it may further have other layers. Examples of layers other than the antistatic layer 3 include an easy-adhesion layer, an easy-slip layer, an anchor layer, an adhesive layer, and a colored layer.
[0023] (Characteristics of double-sided release film) The double-sided release film of the present invention is characterized in that it satisfies the following formulas (1) to (6). Ra<0.1 (1) RpA<2.0 (2) RaB ≧ 0.85 × RaA (3) RpB ≥ 0.85 × RpA (4) 1.5≦HA / HB≦100 (5) 0.15≦HA+HB≦7 (6) In the formulas (1) to (6), RaA represents the center surface average roughness (μm) of the surface of release layer A, RaB represents the center surface average roughness (μm) of the surface of release layer B, RpA represents the center surface maximum protrusion height (μm) of the surface of release layer A in an area of 283 μm x 213 μm, RpB represents the center surface maximum protrusion height (μm) of the surface of release layer B in an area of 283 μm x 213 μm, HA represents the peel force of the surface of release layer A (N / 25 mm width), and HB represents the peel force of the surface of release layer B (N / 25 mm width).
[0024] Regarding formula (1) and formula (2), if RaA is 0.1 μm or more and RpA is 2.0 μm or more, when a resin film is formed on a double-sided release film (carrier film), the high protruding components may cause cissing on the coated surface of the resin film, shape transfer to the resin film may occur, and the resin film layer may have uneven thickness, which may lead to defects due to surface defects in the product. From this viewpoint, the upper limit of RaA is preferably 0.09 μm, more preferably 0.07 μm, and the upper limit of RpA is preferably 1.5 μm, more preferably 1.0 μm.
[0025] A release layer having an RaA of less than 0.1 μm can be obtained, for example, by providing a release layer on the surface of a polyester film having a center surface average roughness of 0.01 to 0.1 μm. The RpA can also be controlled, for example, by adjusting the maximum protrusion height on the surface of the polyester film.
[0026] The lower limit of RaA is not particularly limited, but from the viewpoint of handling in the manufacturing process, it is preferably 0.01 μm, more preferably 0.03 μm. The lower limit of RpA is not particularly limited, but from the viewpoint of handling in the manufacturing process, it is preferably 0.1 μm, more preferably 0.2 μm.
[0027] Regarding formula (3) and formula (4), if RaB is less than 0.85 × RaA and RpB is less than 0.85 × RpA, problems may occur in the handling properties of the film during the manufacturing process. From this viewpoint, it is preferable to satisfy formula (3') and / or formula (4'). RaB ≥ 0.90 × RaA (3') RpB ≥ 0.90 × RpA (4') However, from the viewpoint of suppressing the transfer of protruding components on the B-side to the resin film when the resin film is formed and then wound up, the upper limit of RaB is preferably 0.1 μm, more preferably 0.08 μm, and from the same viewpoint, the upper limit of RpB is preferably 1.5 μm, more preferably 1.0 μm.
[0028] The RaB or RpB can also be controlled by adjusting, for example, the center surface average roughness or maximum projection height of the surface of the polyester film.
[0029] Equations (5) and (6) stipulate the relationship between the peel strength HA (N / 25mm) of the release layer A side (heavy peelable side) and the peel strength HB (N / 25mm) of the release layer B side (lightly peelable side) because the double-sided release film is used for forming adhesive resin films and further as a separator when wound into a tape. Equation (5) stipulates the peel strength ratio between the release layer A side and the release layer B side, and equation (6) stipulates the peel strength level of both release layer surfaces.
[0030] Regarding the value of HA / HB in formula (5) (hereinafter referred to as "peeling force ratio"), when the peeling force ratio is 1.5 or more, the resin film is not easily pulled out smoothly and remains on the reel side. On the other hand, when the peeling force ratio is 100 or less, the peeling force of the release layer A side, i.e., the side on which the resin film remains when pulled out, is not too heavy, and the resin film is pressed onto the adherend and then the carrier film (separator) is easily peeled off cleanly. From this viewpoint, the value of HA / HB is preferably in the range of 4 to 70.
[0031] Regarding formula (6), when HA+HB is 0.15 or more, the double-sided release film on which the resin film is formed has good handling properties, and the resin film can be unwound in a stable state. When HA+HB is 7 or less, excessive stress is unlikely to occur during unwinding, and deformation during unwinding can be easily prevented. From this viewpoint, the value of HA+HB is preferably in the range of 0.2 to 4.
[0032] (polyester) In the present invention, the polyester constituting the polyester-based film used as the base film is a polyester having an aromatic dicarboxylic acid as the main acid component and an aliphatic glycol as the main glycol component. This polyester is substantially linear and can be formed into a film, and it is particularly preferable that the polyester is a polyester that can be formed into a film by melt molding.
[0033] Examples of aromatic dicarboxylic acid components constituting the polyester include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, diphenoxyethanedicarboxylic acid, diphenyldicarboxylic acid, diphenyletherdicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenylketonedicarboxylic acid, and anthracenedicarboxylic acid.
[0034] Examples of the aliphatic glycol component constituting the polyester include polymethylene glycols having 2 to 10 carbon atoms, such as ethylene glycol, diethylene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, and decamethylene glycol, and alicyclic diols, such as 1,4-cyclohexanedimethanol.
[0035] In the present invention, the polyester is preferably one containing alkylene terephthalate and / or alkylene-2,6-naphthalate as the main component.
[0036] Among these polyesters, in particular, polyethylene terephthalate and polyethylene-2,6-naphthalate are of course preferred, as well as, for example, a copolymer in which 80 mol % or more of the total dicarboxylic acid components are terephthalic acid and / or 2,6-naphthalenedicarboxylic acid, and 80 mol % or more of the total glycol components are ethylene glycol. In this case, 20 mol % or less of the total acid components may be the above-mentioned aromatic dicarboxylic acids other than terephthalic acid and / or 2,6-naphthalenedicarboxylic acid, or may be, for example, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, etc.; alicyclic dicarboxylic acids such as cyclohexane-1,4-dicarboxylic acid, etc.
[0037] In addition, 20 mol % or less of the total glycol components may be the above-mentioned glycols other than ethylene glycol, and may also be, for example, aromatic diols such as hydroquinone, resorcin, 2,2-bis(4-hydroxyphenyl)propane, etc.; aliphatic diols having an aromatic ring such as 1,4-dihydroxydimethylbenzene; polyalkylene glycols (polyoxyalkylene glycols) such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.
[0038] The polyester of the present invention also includes those in which a component derived from an oxycarboxylic acid, such as an aromatic oxyacid such as hydroxybenzoic acid or an aliphatic oxyacid such as ω-hydroxycaproic acid, is copolymerized or bonded in an amount of 20 mol % or less based on the total amount of the dicarboxylic acid component and the oxycarboxylic acid component.
[0039] Furthermore, the polyester in the present invention also includes copolymers of tri- or higher functional polycarboxylic acids or polyhydroxy compounds, such as trimellitic acid and pentaerythritol, in an amount that is substantially linear, for example, 2 mol % or less based on the total acid components.
[0040] The polyester can be produced by a method known per se. The polyester has an intrinsic viscosity, measured as a solution in o-chlorophenol at 35° C., of preferably 0.4 to 0.9 dl / g, more preferably 0.5 to 0.7 dl / g, and particularly preferably 0.55 to 0.65 dl / g.
[0041] (Polyester film) The polyester film serving as the substrate of the double-sided release film preferably has a surface shape similar to the surface shape of the double-sided release film after release layer A and release layer B are formed.
[0042] For this reason, the center surface average roughness of the polyester film is preferably 0.01 to 0.10 μm. If the surface roughness exceeds 0.1 μm, it becomes difficult to make the surface roughness RaA of the release layer surface less than 0.1 μm. If the surface roughness is less than 0.01 μm, the surface roughness of the release layer surface is further lower than the surface roughness of the polyester, and the handling properties of the film tend to deteriorate. Depending on the film-forming conditions, RaA does not necessarily equal RaB, so the range of RaB is preferably 0.85×RaA or more.
[0043] In addition, RpA, which is the maximum protrusion of the polyester film, is preferably less than 2.0 μm. If RpA exceeds 2.0 μm, cissing occurs on the resin film coating surface, or the shape is transferred to the resin film, causing poor resin film uniformity. Since RpA=RpB is not always true on both sides of the film depending on the film-forming conditions, RpB is preferably 0.85×RpA or more. If RpB is less than 0.85×RpA, the surface becomes smooth, which may cause problems with handling and winding properties.
[0044] In addition, the polyester-based film preferably has optical properties similar to the optical properties of the double-sided release film after release layer A and release layer B are formed.
[0045] For this reason, the total light transmittance of the polyester-based film is preferably 0 to 50%, and the haze value is preferably 70% or more. Within this range, the total light transmittance and haze value of the double-sided release film are likely to take the values of formulas (7) and (8), and thickness unevenness of the resin film formed on the carrier film is easily observed. In addition, from the viewpoint of confirming that the release film is reliably peeled off in the process of attaching the resin film to the adherend and then peeling off the double-sided release film, the total light transmittance of the polyester-based film is preferably 10 to 30%, and the haze value is preferably 80% or more.
[0046] (Additives) In order to simultaneously satisfy the above-mentioned ranges for the center surface average roughness, total light transmittance, and haze value of such a polyester film, there are methods such as incorporating a filler or pigment into the raw polyester material (kneading method), applying a resin paint containing a filler or pigment to the surface of the polyester film, and forming irregularities on the surface by sandblasting, embossing, etching, etc.
[0047] In the present invention, any of the above methods may be adopted. However, in consideration of the cost and quality of the double-sided release film of the present invention, a kneading method in which fillers, pigments, etc. are incorporated in advance into the polyester raw material is preferred.
[0048] Examples of fillers and pigments to be contained in the polyester include inorganic fillers such as titanium oxide, silicon oxide, barium sulfate, aluminum oxide, magnesium oxide, calcium carbonate, kaolin, talc, etc., organic fillers such as polystyrene resin, acrylic resin, urea resin, melamine resin, etc., and other resin fillers such as polyethylene, polypropylene, ethylene-propylene terpolymer, olefin-based ionomer, etc., and one or more of these may be used. In particular, from the viewpoint of controlling RpA within the range of formula (2), it is preferable to use inorganic fillers (inorganic particles). In addition, antioxidants, ultraviolet absorbers, fluorescent whitening agents, etc. may be contained as necessary.
[0049] The filler or pigment contained in the polyester preferably has an average particle size of 0.1 to 2.0 μm, and more preferably 0.1 to 1.0 μm, particularly for controlling RpA within the range of formula (2).
[0050] The content of the filler or pigment is preferably in the range of 0.05 to 25% by mass, more preferably 0.1 to 22.0% by mass, and even more preferably 1 to 20% by mass, based on the entire polyester film. When the fine particle-containing layer is provided as a surface layer, the fine particle-containing layer preferably contains 0.01 to 15% by mass. When the microvoid-containing layer is provided as an intermediate layer, the filler or pigment may not be contained, but from the viewpoint of controlling the surface unevenness, the fine cavity-containing layer preferably contains 0.01 to 10.0% by mass.
[0051] The incompatible thermoplastic resin to be used as the cavity-forming agent is not particularly limited as long as it is incompatible with the polyester. Here, "incompatible" refers to a state in which compatibility does not occur at the molecular level at the temperature during melt extrusion of the polyester.
[0052] Specific examples of the incompatible thermoplastic resin include polystyrene resins, polyolefin resins, polyacrylic resins, polycarbonate resins, polysulfone resins, and cellulose resins. In particular, polystyrene resins or polyolefin resins such as polymethylpentene and polypropylene are preferred. These resins may be used alone or in combination of two or more.
[0053] When an incompatible thermoplastic resin is contained in the microvoid-containing layer, the total amount of the incompatible thermoplastic resin contained in the microvoid-containing layer is preferably 0.1 to 40 mass %, and more preferably 1 to 25 mass %.
[0054] (Thickness of polyester film, etc.) The polyester film used in the present invention is preferably a biaxially oriented film consisting of a single layer or multiple layers, and preferably has a microvoid-containing layer formed by stretch orientation.
[0055] From the viewpoint of ensuring appropriate handling properties, the total thickness of the polyester film is preferably from 10 to 300 μm, and more preferably from 25 to 200 μm.
[0056] When the polyester film has a three-layer structure of a microparticle-containing layer / microvoid-containing layer / microparticle-containing layer, the thickness of each microparticle-containing layer is preferably 3 to 25% of the total, more preferably 5 to 15%, from the viewpoint of controlling the surface shape and optical properties of the polyester film.When the polyester film has a two-layer structure of a microparticle-containing layer / microvoid-containing layer, the thickness of the microparticle-containing layer is preferably 3 to 25% of the total, more preferably 5 to 15%, from the same viewpoint.
[0057] (Manufacturing method of polyester film) The biaxially oriented polyester can be obtained by a conventionally known method.
[0058] For example, a polyester is melt-extruded at a temperature of melting point (Tm: °C) to (Tm+70) °C to obtain an unstretched film, and the unstretched film is stretched in one axial direction (longitudinal or transverse direction) at a temperature of (Tg-10) to (Tg+70) °C (where Tg is the glass transition temperature of the polyester) at a ratio of 2.5 times or more, preferably 3 times or more, and then stretched in a direction perpendicular to the stretching direction at a temperature of Tg to (Tg+70) °C at a ratio of 2.5 times or more, preferably 3 times or more. If necessary, the film may be stretched again in the longitudinal direction and / or transverse direction. Thus, the total stretching ratio is preferably 9 times or more in terms of area stretching ratio, more preferably 12 to 35 times, and particularly preferably 15 to 30 times. Furthermore, the biaxially oriented film can be heat-set at a temperature of (Tg+70) °C to (Tm-10) °C, and is preferably heat-set at, for example, 180 to 250 °C. The heat-setting time is preferably 1 to 60 seconds.
[0059] When producing a biaxially oriented polyester consisting of two or more layers, the raw materials for each layer are melted and then co-extruded to obtain a laminated unstretched film, and then the same steps are carried out to produce the film.
[0060] When producing a biaxially oriented polyester having a three-layer structure of a microparticle-containing layer / microvoid-containing layer / microparticle-containing layer, a cavity-forming agent can be added to the raw material for the microvoid-containing layer, and microvoids can be formed by stretching the laminated unstretched film.
[0061] (Release layer) The release layer A and the release layer B (hereinafter collectively referred to as "release layer") in the present invention are not particularly limited as long as their properties satisfy the above formulas (1) to (6). For example, a coating liquid containing a silicone resin, silicone oil, fluororesin, fluorooil, various waxes, or other organic resins such as polyester resin, alkyd, polyurethane, acrylic, melamine, polyvinyl acetal, etc. modified with silicone or fluorine, or a coating liquid containing a silicone oil, fluorooil, or various waxes added to an organic resin may be used.
[0062] Among them, curable silicone resins are preferred from the viewpoint of heat resistance, and as the curable silicone resin, any reaction type can be used, such as a condensation reaction type, an addition reaction type, an ultraviolet or electron beam curable type, etc. These curable silicone resins may be used alone or in combination of two or more types.
[0063] The curing reactions of various silicone resins can be illustrated as follows.
[0064] [ka]
[0065] An example of the condensation reaction type silicone resin is one in which a three-dimensional crosslinked structure is formed by condensing polydimethylsiloxane having a terminal -OH group and polydimethylsiloxane (hydrogensilane) having a terminal -H group using an organotin catalyst (e.g., an organotin acylate catalyst).
[0066] An example of an addition reaction type silicone resin is one in which polydimethylsiloxane having vinyl groups introduced at the ends is reacted with hydrogen silane, a crosslinking agent, in the presence of a platinum catalyst to form a three-dimensional crosslinking structure.
[0067] Examples of UV-curable silicone resins include the most basic type that utilizes the same radical reaction as normal silicone rubber crosslinking, those that introduce acrylic groups and photo-cure, those that use UV light to decompose onium salts to generate strong acids that then cleave epoxy rings to crosslink, and those that crosslink by the addition reaction of thiols to vinyl siloxanes. Electron beams have more energy than UV light, and crosslinking reactions occur by radicals without the use of initiators as in the case of UV curing.
[0068] The curable silicone resin preferably has a degree of polymerization of about 500,000 to 200,000, and more preferably about 1,000 to 100,000. Specific examples of such a resin include KS-718, -774, -775, -778, -779H, -830, -835, -837, -838, -839, -841, -843, -847, -847H, X-62-2418, -2422, -2125, -2492, -2494, -470, -2366, -630, X-92-140, -128, KS-723A·B, -705F, -708A, -883, -709, and -719, all of which are manufactured by Shin-Etsu Chemical Co., Ltd.; and TPR-6701 and -6702, all of which are manufactured by Toshiba Silicones Co., Ltd. Examples of silicone rubbers that can be used include, -6703, -3704, -6705, -6722, -6721, -6700, XSR-7029, YSR-3022, YR-3286, DK-Q3-202, -203, -204, -210, -240, -3003, -205, -3057, SFXF-2560 manufactured by Dow Corning Corporation, SD-7226, -7320, -7229, BY24-900, -171, -312, -374, SRX-375, SYL-OFF23, SRX-244, SEX-290 manufactured by Dow Corning Toray Silicone Co., Ltd., and SILCOLEASE425 manufactured by ICI Japan Co., Ltd. Furthermore, silicone resins described in JP-A-47-34447 and JP-B-52-40918 can also be used.
[0069] The coating method for forming the curable silicone resin coating film on the surface of the film can be a conventional method such as a bar coating method, a doctor blade method, a reverse roll coating method, or a gravure roll coating method.
[0070] Drying and curing (thermal curing, UV curing, etc.) of the coating film can be carried out separately or simultaneously. When they are carried out simultaneously, they are preferably carried out at 100°C or higher. The conditions for drying and curing are preferably 100°C or higher and 30 seconds or longer. Drying temperatures below 100°C and curing times below 30 seconds are not preferred because the coating film will not be cured completely and will tend to fall off.
[0071] The thickness of the release layer is not particularly limited, but is preferably in the range of 0.005 to 0.5 μm, more preferably 0.05 to 0.5 μm. If the thickness is 0.005 μm or more, sufficient release properties are easily obtained, and if it is 0.5 μm or less, the curing time can be shortened, which is convenient in terms of production.
[0072] In addition, the method for forming the release layer in the present invention is not particularly limited, but for example, the release layer can be formed in the following manner: That is, an aqueous coating composition obtained by dissolving trialkoxysilane represented by the following general formula (1) and tetraalkoxysilane represented by the following general formula (2) in water through hydrolysis is applied to at least one side of a polyester film, and then dried to produce a release film.
[0073] The coating may be performed in a normal coating process, that is, a process in which the composition is applied to a polyester film separately from the manufacturing process of the film. However, since this process is prone to entraining dirt, dust, etc., it is desirable to perform the coating in a clean atmosphere. From this viewpoint, coating during the manufacturing process of the polyester film is preferred. In particular, it is preferred to apply the composition as an aqueous coating composition to the polyester film before the crystal orientation is completed during this process.
[0074] R 1 -Si(-OR 2 ) 3 (1) (In the formula, R 1 is an alkyl group having 1 to 5 carbon atoms, R 2 represents an alkyl group having 1 to 2 carbon atoms. Si(-OR 3 ) 4 (2) (In the formula, R 3 represents an alkyl group having 1 to 2 carbon atoms. Here, polyester-based films before the completion of crystal orientation include unstretched films in which polyester is heat-melted and formed into a film as is; uniaxially stretched films in which unstretched films are oriented in either the longitudinal direction (length direction) or the transverse direction (width direction); and films that have been oriented by low-magnification stretching in both the longitudinal and transverse directions (biaxially stretched films before the final re-stretching in the longitudinal or transverse direction to complete the orientation crystallization).
[0075] The coating method may be any known coating method, such as kiss coating, bar coating, die coating, reverse coating, offset gravure coating, Mayer bar coating, gravure coating, roll brushing, spray coating, air knife coating, impregnation, and curtain coating, which may be used alone or in combination.
[0076] The polyester film coated with the aqueous coating composition before completing the crystal orientation is dried and guided to a process of stretching, heat setting, etc. For example, a polyester film coated with the aqueous coating composition and uniaxially stretched longitudinally is guided to a stenter and transversely stretched and heat set. During this process, the aqueous coating composition is dried and thermally crosslinked.
[0077] The conditions for orientation crystallization of polyester-based films, such as conditions for stretching, can be carried out under conditions that have been accumulated in the art, but the heat setting temperature is preferably adjusted so that the melting subpeak temperature (Tsm) of the film is preferably 180°C or higher, more preferably 200°C or higher, and even more preferably 210°C or higher. The melting subpeak temperature (Tsm) here is a small endothermic peak that appears before the crystal melting of polyester by differential scanning calorimetry (DSC), and this melting subpeak (Tsm) is observed as a small peak at a temperature equivalent to the heat setting temperature of the film, and occurs due to the melting of an incomplete part (pseudo crystal) of the crystal structure formed by the heat setting treatment. If the Tsm is below 180°C, the amount of heat required to harden the release layer in the present invention is large, so that a sufficient amount of heat is not supplied to harden the coating film, resulting in insufficient crosslinking and failure to develop the desired release properties. In addition, since the adhesive strength of the resin film varies depending on the resin used in the resin film, the degree of curing of the resin, and even the film thickness, it is necessary to adjust it within a range that satisfies formula (6). In addition to adjusting the combination of release agents, the amount of curing catalyst, and the coating thickness as described above, at least one of the following four methods can be used to control the peel strength for silicone-based release agents.
[0078] (1) A silicone resin having the following D unit, T unit and / or Q unit structure is blended into a polydimethylsiloxane polymer to adjust the concentration of methyl groups in the release layer and increase the surface tension. The blending ratio of this silicone resin is preferably 20 to 60 mass% in terms of solid content concentration. If the blending ratio is less than 20 mass%, the wettability of the release layer may be poor, and if it exceeds 60 mass%, the release layer may become too hard and have poor abrasion resistance, which is not preferable.
[0079] [ka]
[0080] In the D and T units, R represents an alkyl group such as a methyl group, or an aromatic hydrocarbon group such as a phenyl group.
[0081] (2) A silica filler is blended into a polydimethylsiloxane polymer to adjust the concentration of -Si-OH groups in the release layer to be high, thereby increasing the surface tension. The silica filler preferably has an average particle size of 1 μm or less. If the average particle size is 1 μm or less, the release layer is less likely to be scraped off when the film is run in the processing step, which is preferable. The blending ratio of the silica filler is preferably 0.1 to 1 mass% in terms of solid content concentration. If the blending ratio is 0.1 mass% or more, the desired wettability is easily obtained, and if it is 1 mass% or less, the silica filler is less likely to be scraped off from the release layer, which is preferable.
[0082] (3) Modified polydimethylsiloxane in which some of the methyl groups in the polydimethylsiloxane polymer are replaced with bulky phenyl groups. Due to the steric hindrance of the phenyl groups, for example, the rotational motion around the -Si-O-Si- bond in the polymer is suppressed, and as a result, the concentration of methyl groups on the surface of the release layer is reduced, so that the surface tension can be increased. The substitution ratio of this phenyl group is preferably 20 to 60 mol %. If this substitution ratio is 20 mol % or more, the desired releasability is easily obtained, and if it is 60 mol % or less, the releasability between the release layer and various pressure sensitive adhesives and various sheets is good.
[0083] (4) Modified polydimethylsiloxane obtained by reacting a polydimethylsiloxane polymer having a relatively high concentration of reactive groups such as silanol groups and methoxy groups with an organic resin having a hydroxyl group in the molecule (e.g., alkyd resin, polyester resin, acrylic resin, etc.). The proportion of dimethylsiloxane components in this modified polydimethylsiloxane is preferably 10 to 30% by mass. If this proportion is 10% by mass or more, the mold releasability is good, and if it is 30% by mass or less, the desired mold releasability is easily obtained.
[0084] (Antistatic layer) Generally, release films on which a resin film has been formed are prone to generating static electricity when they come into contact with rolls in the process, which can cause fatal damage to electrical and electronic materials. Specifically, static electricity generated during the friction or contact peeling process between the transport roll and the release film can cause electrostatic patterns, and positional deviations can occur during the attachment or lamination process due to static electricity caused by peeling.
[0085] Therefore, in the present invention, an antistatic layer can be provided on at least one side of the polyester film before providing release layers on both sides of the film, which reduces charging during unwinding and running, and also reduces charging problems when the film is unwound and used as a resin film.
[0086] In the present invention, the antistatic layer has a surface resistivity of 5×10 after the release layer is provided. 4 ~5×10 12 Ω / □ is preferable, and 5×10 5 ~5×10 10 It is more preferably Ω / □.
[0087] The antistatic layer is not particularly limited, but preferably contains at least one selected from the group consisting of metal oxide fine particles, conductive polymers, and polymers to which a quaternary ammonium salt is added. The means for forming the antistatic layer is not particularly limited, and known methods such as coating, vacuum deposition, and lamination can be used, but from the viewpoint of cost, it is preferable to provide the layer by coating a coating liquid containing an antistatic agent.
[0088] Metal oxide particles include antimony-doped tin oxide (ATO), ZnO, and CeO. 2 , Sb 2 O 2 , SnO 2 Indium tin oxide, often abbreviated as ITO, 2 O 3 , Al 2 O 3and aluminum-doped zinc oxide (AZO). The fine particles refer to particles of a size of 1 micron or less, that is, submicron size, and preferably have an average particle size of 0.1 nm to 0.1 μm. According to a preferred embodiment of the present invention, the primary particle size of the conductive fine particles is preferably about 30 to 70 nm, and the secondary particle size is preferably about 200 nm or less.
[0089] Examples of conductive polymers include polyacetylene, which is an aliphatic conjugated system, poly(paraphenylene), which is an aromatic conjugated system, polypyrrole, polythiophene, which is a heterocyclic conjugated system, polyaniline, which is a heteroatom-containing conjugated system, and poly(phenylenevinylene), which is a mixed conjugated system.Further examples include a multi-chain conjugated system, which is a conjugated system having multiple conjugated chains in the molecule, and a conductive composite, which is a polymer in which the above-mentioned conjugated polymer chain is grafted or block-copolymerized to a saturated polymer.
[0090] As the polymer to which a quaternary ammonium salt is added, a polymerizable compound such as a monomer or oligomer having a quaternary ammonium group and capable of being polymerized by ionizing radiation, or an organometallic compound such as a coupling agent having a functional group capable of being polymerized by ionizing radiation can be used.
[0091] In order to improve the strength of the resulting coating film, an alkoxysilane or acyloxysilane may be further added to the antistatic layer. These silane compounds are present in the coating film in the form of a reaction product obtained by hydrolysis and subsequent condensation reaction.
[0092] Examples of these silane compounds include trialkoxysilanes having a reactive functional group other than an alkoxy group, such as methyltriacetoxysilane, dimethyldiacetoxysilane, trimethylacetoxysilane, tetraacetoxysilane, tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetraisobutoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, phenyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and vinyltriethoxysilane.
[0093] The antistatic layer may contain a surfactant to improve the appearance. Examples of the surfactant include nonionic surfactants such as polyoxyethylene octylphenyl ether, polyoxyethylene alkyl ether, and polyoxyethylene sorbitan fatty acid ester, and fluorine-based surfactants such as fluoroalkyl carboxylic acid, perfluoroalkyl carboxylic acid, perfluoroalkyl benzene sulfonic acid, perfluoroalkyl quaternary ammonium, and perfluoroalkyl polyoxyethylene ethanol.
[0094] The antistatic layer may contain lubricants, dyes, ultraviolet absorbers, crosslinking agents, silane coupling agents, etc., as necessary, within the limits not impairing the object of the present invention.
[0095] Methods for coating and laminating an antistatic layer on the surface of a substrate film include gravure roll coating, reverse roll coating, knife coater, dip coating, spin coating, etc., but there is no particular restriction on the coating method suitable for the conductive composition. In addition, the antistatic layer can be provided by an in-line coating method in which a coating layer is provided during the film production process, or an off-line coating method in which a coating layer is provided after the film is produced.
[0096] The drying temperature for forming the antistatic layer is usually 60° C. to 150° C., preferably 90° C. to 140° C. If the temperature is 60° C. or higher, the treatment can be performed in a short time, which is preferable from the viewpoint of improving productivity. On the other hand, if the temperature is 150° C. or lower, the flatness of the film can be maintained, which is preferable.
[0097] The thickness of the antistatic layer is preferably 0.005 μm or more and 5 μm or less. More preferably, it is 0.01 μm or more and 1 μm or less, and even more preferably, it is 0.01 μm or more and 0.2 μm or less. When the thickness of the antistatic layer is 0.005 μm or more, it is preferable because an antistatic effect can be obtained. On the other hand, when it is 5 μm or less, it is preferable because there is no risk of impairing the releasability.
[0098] (Uses of double-sided release film) The double-sided release film of the present invention can be used in manufacturing processes such as forming double-sided pressure-sensitive adhesive tapes, forming green sheets for ceramic capacitors, forming anisotropic conductive films, forming insulating resin sheets for circuit boards, etc. Specifically, for example, it can be used as a carrier film in the process of forming resin films that are the raw materials for various functional sheets, or as a separator during winding.
[0099] For example, anisotropic conductive films can be manufactured by coating and drying an adhesive varnish made by mixing and dispersing conductive particles in an insulating adhesive made by mixing an insulating resin such as epoxy resin with a coupling agent, a curing agent, and a curing accelerator onto a carrier film (separator). EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples and comparative examples. In the present invention, the properties were measured and evaluated by the following methods. In the following, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0101] (a) Film and thickness of each layer The film was cut using a microtome to obtain a cross section perpendicular to the film surface. This cross section was coated with a platinum-palladium alloy by sputtering to prepare an observation sample. The film cross section was observed using a scanning electron microscope (Hitachi, S-510 model) and photographed at an appropriate magnification so that the entire thickness of the film was covered in one field of view. From this image, the thickness of each layer was measured using a scale. Measurements were performed on three independently prepared cross section samples, and the average value was taken as the layer thickness of the laminated film.
[0102] (b) Intrinsic viscosity (IV) The polyester resin was crushed, dried, and then dissolved in OCP. The intrinsic viscosity (intrinsic viscosity) of the polyester resin was calculated using an automatic viscosity measuring device (Rigosei VMC-252).
[0103] (c) Average particle size Using a scanning electron microscope (Hitachi S-4700), particles are measured at magnifications of 10,000 to 100,000, the particle sizes (average value of the long and short diameters) of 1,000 particles are read, and the average particle size of the 1,000 particles is calculated.
[0104] (1) Center surface roughness (Ra), center surface maximum protrusion height (Rp) A non-contact three-dimensional surface roughness meter (ZYGO: New View 7300) was used to measure the surface area of 283 μm × 213 μm (=0.0603 mm) at a measurement magnification of 25 times. 2 The surface analysis software Metro Pro built into the roughness meter was used to determine the center surface average roughness (Ra) and center surface maximum protrusion height (Rp). At that time, measurements were taken three times at different measurement points, and the average values were calculated.
[0105] (2) Peeling strength A polyester adhesive tape (Nitto Denko Corporation, Knit-31B) was attached to the release layer surface of the film and pressed with a 5 kg pressure roller, after which the peel strength (HA, HB) at 180° between the release layer and the adhesive tape was measured with a tensile tester.
[0106] (3)Residual adhesion rate A polyester adhesive tape (Nitto Denko Corporation, Knit-31B) was adhered to a cold-rolled stainless steel plate (SUS304) specified in JIS G4305 using a 5 kg pressure roller and maintained for 30 seconds. The peel strength was then measured at 180° and used as the basic adhesive strength (f0).
[0107] Next, a new polyester adhesive tape was applied to the release layer surface of the sample film with a 5 kg pressure roller, and after maintaining the pressure for 30 seconds, the polyester adhesive tape was peeled off. The peeled polyester adhesive tape was then applied to the stainless steel plate under the same conditions, and the peel strength of the applied portion was measured and taken as the residual adhesive strength (f). The residual adhesive rate was calculated from the obtained basic adhesive strength (f0) and residual adhesive strength (f) using the following formula.
[0108] Residual adhesion rate (%)=(f / f0)×100
[0109] (4) Surface resistivity Using a resistivity meter (model number 5451) manufactured by ADC Corporation, the surface resistivity was measured after 1 minute at an applied voltage of 500 V under the conditions of a measurement temperature of 23° C., measurement humidity of 65% RH and 45% RH, according to the double ring method described in JIS K6271 (2008). The measurement was performed on the release layer surface of the antistatic layer.
[0110] (5) Surface condition of the resin film (coatability) A double-sided release film (film width: 1.2 m, length: 500 m) was unwound from a roll, and a resin coating having the following composition was applied to side A of the release layer. The film was then heated at 120°C for 5 minutes to volatilize the solvent and form a resin film with a thickness of 0.5 μm. The surface condition was then observed and evaluated according to the following criteria.
[0111] ◯: No repelling was observed on the resin film surface (resin film surface condition was good).
[0112] ×: Cracks were observed on the surface of the resin film (poor surface condition of the resin film). <Resin paint> An adhesive resin composition having the following composition was adjusted to a solid content concentration of 5% to obtain a resin coating material.
[0113] Liquid epoxy resin (Epicoat 828, manufactured by Mitsubishi Chemical Corporation) 1 part by weight Phenoxy resin (PKHH, Gabriel Phenoxies) 2 parts by mass Hardener (Amicure PN-23, manufactured by Ajinomoto Fine-Techno Co., Ltd.) 0.3 parts by weight Solvent (MEK / toluene = 1 / 1) 57 parts by weight (6) Resin film peeling condition The above resin coating was applied to the release layer A surface, and then heated at 120°C for 5 minutes to volatilize the solvent and form a resin film with a thickness of 0.5 µm. Thereafter, the release layer B was placed on top of the resin film so as to be in contact with the resin film, and a pressure of 2 kg / cm was applied. 2The sample was subjected to a pressure of 1000 psi and aged for 17 hours at 50° C. After aging, release layer B was peeled off, and the surface of release layer B was observed and evaluated according to the following criteria. ◯: No resin remains on surface B of release layer (resin film peeled off well). ×: Resin remains on surface B of release layer (poor resin film peeling).
[0114] [Example 1] A composition consisting of 90% by mass of polyester (intrinsic viscosity: 0.63 dl / g, Tg: 79°C, Tm: 253°C) made from terephthalic acid and ethylene glycol and 10% by mass of silica (average particle size: 1.7 μm) was melt-extruded onto a rotating cooling drum maintained at 20°C to form an unstretched film, which was then stretched 3.6 times in the machine axis direction and then 3.9 times in the transverse direction to obtain a biaxially stretched polyester film with a thickness of 50 μm.
[0115] A release coating A (for release layer A) having the following composition was applied to one side of this film, and release coating B (for release layer B) was applied to the other side to obtain a double-sided release film. The release coating was cured at 150°C for 30 seconds, and the thickness of the release layer was 0.2 μm on both sides. The properties of this double-sided release film are shown in Table 1.
[0116] <Release paint A> BY24-400 (Toray Dow Corning Silicone Co., Ltd.) 100 parts by weight Solvent (toluene / MEK=1 / 1) 1400 parts by weight SRX-212 (Toray Dow Corning Silicone Co., Ltd.) 2 parts by weight <Release paint B> KS-847H (Shin-Etsu Chemical Co., Ltd.) 100 parts by mass Solvent (toluene / MEK=1 / 1) 1400 parts by weight PL-50T (Shin-Etsu Chemical Co., Ltd.) 2 parts by weight [Example 2] A double-sided release film was produced in the same manner as in Example 1, except that release coating C (for release layer A) was used instead of release coating A. The properties of this double-sided release film are shown in Table 1. The release coating C had the following composition.
[0117] <Release paint C> KS-847H (Shin-Etsu Chemical Co., Ltd.) 100 parts by mass KS-3800 (Shin-Etsu Chemical Co., Ltd.) 25 parts by weight Solvent (MEK / toluene = 1 / 1) 1400 parts by weight PL-50T (Shin-Etsu Chemical Co., Ltd.) 2 parts by weight [Example 3] A double-sided release film was produced in the same manner as in Example 1, except that release coating D (for release layer A) was used instead of release coating A. The properties of this double-sided release film are shown in Table 1. The release coating D had the following composition.
[0118] <Release paint D> KS-847H (Shin-Etsu Chemical Co., Ltd.) 100 parts by mass KS-3800 (Shin-Etsu Chemical Co., Ltd.) 50 parts by weight Solvent (MEK / toluene = 1 / 1) 1400 parts by weight PL-50T (Shin-Etsu Chemical Co., Ltd.) 2 parts by weight [Example 4] A double-sided release film was obtained in the same manner as in Example 1, except that an antistatic layer shown below was provided with a thickness of 0.1 μm before applying release coating A, and then release coating B was applied. The properties of this double-sided release film are shown in Table 1.
[0119] <Antistatic paint> Colcoat SP-2014 (Colcoat Co., Ltd., 7% by weight aqueous dispersion of antimony-doped tin oxide) 100 parts by weight Tetraethyl silicate (Wako Pure Chemical Industries, Ltd.) 10 parts by mass 100 parts by mass of water Surfactant (Kao Corporation, Emulgen 1108) 20 parts by weight [Example 5] A release film was obtained in the same manner as in Example 1, except that 20% by mass of calcium carbonate particles having an average particle size of 0.5 μm was used instead of 10% by mass of silica (average particle size: 1.7 μm) in Example 1. The properties of this release film are shown in Table 1.
[0120] [Example 6] A release film was obtained in the same manner as in Example 5, except that the antistatic layer used in Example 4 was provided with a thickness of 0.1 μm before applying the release coating A. The properties of this release film are shown in Table 1.
[0121] [Example 7] A release film was obtained in the same manner as in Example 1, except that 15% by mass of silica particles having an average particle size of 0.3 μm was used instead of 10% by mass of silica (average particle size: 1.7 μm) in Example 1. The properties of this release film are shown in Table 1.
[0122] [Example 8] A release film was obtained in the same manner as in Example 7, except that the antistatic layer used in Example 4 was provided with a thickness of 0.1 μm before applying the release coating A. The properties of this release film are shown in Table 1.
[0123] [Comparative Example 1] A double-sided release film was produced in the same manner as in Example 1, except that release coating B (for release layer A) was used instead of release coating A. The performance of this double-sided release film is shown in Table 1.
[0124] [Comparative Example 2] A release film was obtained in the same manner as in Example 1, except that 10% by mass of titanium oxide particles having an average particle size of 3.0 μm was used instead of 10% by mass of silica (average particle size: 1.7 μm) in Example 1. The properties of this release film are shown in Table 1.
[0125] [Comparative Example 3] A release film was obtained in the same manner as in Example 1, except that 0.03 mass% of titanium oxide particles having an average particle size of 6.0 μm were used instead of 10 mass% of silica (average particle size: 1.7 μm) in Example 1. The properties of this release film are shown in Table 1.
[0126] [Table 1]
[0127] In Table 1, the measurement surfaces are indicated as surface A of release layer A and surface B of release layer B.
[0128] As is clear from Table 1, in Examples 1 to 8 which satisfied the formulas (1) to (6), even when a thinner resin film was formed, the surface condition and peeling condition of the resulting resin film were good.
[0129] In contrast, the peeling state of the resin film obtained in Comparative Example 1, which did not satisfy formulas (5) and (6), was poor. Also, the surface state of the resin film obtained in Comparative Example 2, which did not satisfy formulas (1) and (2), and Comparative Example 3, which did not satisfy formula (2), were poor. [Industrial Applicability]
[0130] The double-sided release film of the present invention can be used, for example, as a carrier film in the process of forming a resin film having adhesive properties, and can also be used as a separator during winding or when using the resin film. [Explanation of symbols]
[0131] 1. Polyester film 2A Release layer A 2B Release layer B 3 Antistatic layer 5 Resin film
Claims
1. The release layer A includes a polyester film and a release layer B in this order, A double-sided release film for forming an anisotropic conductive film, characterized in that it satisfies the following formulas (1) to (6): RaA<0.1...(1) RpA<2.0...(2) RaB ≧ 0.85 × RaA ... (3) RpB ≧ 0.85 × RpA (4) 1.5≦HA / HB≦100 (5) 0.15≦HA+HB≦7 (6) In the formulas (1) to (6), RaA represents the center surface average roughness (μm) of the surface of release layer A, RaB represents the center surface average roughness (μm) of the surface of release layer B, RpA represents the center surface maximum protrusion height (μm) of the surface of release layer A in an area of 283 μm × 213 μm, RpB represents the center surface maximum protrusion height (μm) of the surface of release layer B in an area of 283 μm × 213 μm, HA represents the peel force (N / 25 mm width) of the surface of release layer A, and HB represents the peel force (N / 25 mm width) of the surface of release layer B.
2. 2. The double-sided release film according to claim 1, wherein the release layer A and the release layer B contain a cured product of an addition reaction type silicone resin.
3. An antistatic layer is included between at least one of the release layer A and the release layer B and the polyester film, and the surface resistivity of the surface of the release layer on the side where the antistatic layer is provided is 5×10 4 ~5×10 12 3. The double-sided release film according to claim 1 or 2, wherein the resistivity is Ω / □.
4. The double-sided release film according to any one of claims 1 to 3, wherein the polyester film contains inorganic particles having an average particle size of 0.1 to 2.0 µm.
5. 5. The double-sided release film according to claim 4, wherein the content of the inorganic particles is 0.05 to 25% by mass.
6. 4. The double-sided release film according to claim 3, wherein the antistatic layer comprises at least one selected from the group consisting of conductive polymers, metal oxide fine particles, and polymers to which a quaternary ammonium salt has been added.
Citation Information
Patent Citations
Mold release film
JP2002331614A
Release film
JP4495880B2
Release film for use in producing green sheet
WO2013161422A1